Effect of fly ash on mechanical properties of magnesium oxychloride cement under water attack. (30th December 2019) - Guo, Yingying; Zhang, Yixia; Soe, Khin; Hutchison, Wayne D.; Timmers, Heiko; Poblete, Myra R.
Abstract: As an eco‐friendly construction material, magnesium oxychloride cement (MOC) has attracted much research interest in recent decades, however, its mechanical properties degrade severely under water attack, which has prevented its wide application in engineering structures. As a widely used mineral waste, fly ash has been applied in civil engineering for decades. The active SiO2 in fly ash is considered to be conductive to improve the water resistance of MOC. In this paper, the influence of fly ash on the mechanical properties of MOC is investigated, especially when subject to water attack. First, the basic mix design of the MOC with a suitable combination of the molar ratios of MgO/MgCl2 and H2 O/MgCl2 is developed, and the developed basic MOC mix is modified by adding fly ash to improve its water resistance. Second, the physical and mechanical properties of both the basic MOC and the fly ash modified MOC, such as compressive strength, Young's modulus, flexural strength cured at room temperature, and immersed in water for 28 days at room temperature (25°C) are determined. It is found that the incorporation of fly ash decreases the workability or fluidity, retards the setting time, but improves the compressive strength and water resistance of the MOC. The techniques of X‐ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis/differential scanning calorimetry, scanning electron microscopy, and mercury intrusion porosimetry are applied to the MOC specimens to discover the mechanism by which fly ash affects on the water resistance of MOC. The microscale analysis shows that the addition of fly ash optimizes the pore distribution in MOC resulting in a denser structure, which contributes to the water repellence.